Revision of Immunopathogenesis and Laboratory Interpretation for Food Allergy in Atopic Dermatitis - Noh, Geunwoong; Ho Lee, Jae (Inflammation & Allergy-Drug Targets (Discontinued), 2012)
Atopic dermatitis is an allergic inflammatory skin disease that is characterized by late eczematous skin lesions which result from non-IgE-mediated immune responses. It is well known that food allergy is an important cause of atopic dermatitis. Moreover, with recent advances in the diagnosis and treatment of food allergy, it becomes possible to elucidate the role of IgE- and non-IgE-mediated food allergies. Interprerations for blood eosinophil counts and total serum IgE levels are updated based on the immunopathogenesis of AD relating with these IgE- and non-IgE-mediated food allergies. The clinical significances of skin prick test and allergen-specific IgE are re-evaluated according to the out-to in and in-to out sensitization. Atopic march is reconsturcted by the sequential sensitization of foods and aeroallergens. In this review, the revized immunopathogenesis and relevant interpretations of food allergy in atopic dermatitis are described for the evaluation of precise clinical status of AD.
Keywords: Atopic dermatitis